2020
DOI: 10.1002/alz.12105
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of the 5th Canadian Consensus Conference on the diagnosis and treatment of dementia

Abstract: Since 1989, four Canadian Consensus Conferences on the Diagnosis and Treatment of Dementia (CCCDTD) have provided evidence‐based dementia guidelines for Canadian clinicians and researchers. We present the results of the 5th CCCDTD, which convened in October 2019, to address topics chosen by the steering committee to reflect advances in the field, and build on previous guidelines. Topics included: (1) utility of the National Institute on Aging research framework for clinical Alzheimer's disease (AD) diagnosis; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
197
0
27

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 158 publications
(227 citation statements)
references
References 117 publications
3
197
0
27
Order By: Relevance
“…[11][12][13] Measuring each individual's degree of frailty may help identify those individuals without cognitive impairment most likely to develop MCI, 14 and those with MCI most likely to progress to dementia. 15 Critically, despite recent recommendations in support of preventing and mitigating frailty 16 -chiefly through lifestyle interventions that overlap with those proposed for dementia-it is not yet known whether frailty plays an equal role in dementia development in relation to a genetic predisposition to dementia. Recent evidence is mixed about whether a healthy lifestyle reduces dementia risk in those at high genetic risk.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Measuring each individual's degree of frailty may help identify those individuals without cognitive impairment most likely to develop MCI, 14 and those with MCI most likely to progress to dementia. 15 Critically, despite recent recommendations in support of preventing and mitigating frailty 16 -chiefly through lifestyle interventions that overlap with those proposed for dementia-it is not yet known whether frailty plays an equal role in dementia development in relation to a genetic predisposition to dementia. Recent evidence is mixed about whether a healthy lifestyle reduces dementia risk in those at high genetic risk.…”
Section: Introductionmentioning
confidence: 99%
“…They may also be considered for the treatment of vascular cognitive impairment and in selected parkinsonian patients. 13,46 But in Poland, donepezil treatment is reimbursed only in AD, Lewy Body dementia, and PDD, whereas rivastigmine is reimbursed only in AD. Finally, it should also be taken into account that drugs used in dementia have no causal effect but act only symptomatically.…”
Section: Discussionmentioning
confidence: 99%
“…Their effectiveness is limited, may change over time, or side effects may prevent their use in some patients. 13 This can also affect their prescribing, and high rates of non-persistence in dementia patients who received a prescription for cognitive enhancers. Research carried out in Germany, for example, showed that only 69.9% of patients aged >70 who received a prescription for anti-dementia medication were on it six months after initiation of treatment, and only 56.2% after 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…History from an informant is essential to a thorough and reliable cognitive assessment, given the role of anosognosia. Consistent with the recent Fifth Canadian Consensus Conference on Diagnosis and Treatment of Dementia (CCCDTD5) recommendations, cognitive assessments include information on cognition, function, and behavior, and fundamentally both patient or care partner are required as sources of information 16 . With the patient's consent, history can be obtained by phone from an informant located in a separate, private space or during a separate appointment.…”
Section: Logistical Recommendations For Setting Up and Administering mentioning
confidence: 99%